A method for preparing perovskite composite materials based on light induction

The preparation of perovskite composite materials under invisible light was solved by light-induced method, which solved the problem of difficulty in stability and size regulation of perovskite composite materials, and achieved green and environmentally friendly synthesis and efficient perovskite nanocrystal generation, which was suitable for Potential applications of display devices.

CN117025217BActive Publication Date: 2025-01-07ZHEJIANG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310900516.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-21
Publication Date
2025-01-07
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

In the prior art, perovskite composite materials have poor stability and are difficult to regulate the size of perovskites. In common synthesis methods, harmful polar solvents need to be introduced to affect the environment and health and safety of the material.

Method used

The perovskite composite material was prepared by light-induced method. By reacting halogenated alkanes with lead and cesium precursors under invisible light, CsPbX3 nanocrystals were generated, which avoided the use of high boiling point and toxic reagents, and adjusted the photon dose and wavelength to control the stability and size of the material.

Benefits of technology

The stability of perovskite composite materials is improved, the use of harmful solvents is avoided, the synthesis process is simplified, the water stability and optical properties of the material are improved, and it is suitable for lighting applications of display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117025217B_ABST
    Figure CN117025217B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a perovskite composite material based on light induction, which comprises the following steps: preparing a mixed precursor solution containing lead oleate and cesium oleate; preparing a mixed precursor powder containing a covalent organic framework material, lead oleate and cesium oleate; adding a halogenated alkane to the mixed precursor solution or the mixed precursor powder, and reacting under the action of invisible light, and after the reaction is completed, post-processing is performed to obtain a perovskite composite material CsPbX3 NCs or CsPbX3@S-COFs. The present invention has the advantages of mild and simple preparation conditions, green and environmental protection, ability to improve the stability of the composite material, and convenience in regulating the size of the perovskite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optoelectronic materials, and in particular to a method for preparing a perovskite composite material based on light induction. Background Art

[0002] As a new type of nano-luminescent material, perovskite has superior optical properties different from macroscopic materials, including adjustable luminescent color, narrow emission spectrum, high luminescent efficiency and many other advantages, thus becoming a research hotspot in the field of luminescence. However, compared with traditional II~VI cadmium quantum dots, the stability of perovskite luminescent materials is still poor and cannot meet the standards of commercial display, which also limits the future display application and development of perovskite. In recent years, porous materials have been widely studied as a matrix to improve the stability of perovskite luminescent materials, including mesoporous silica, mesoporous titanium dioxide, molecular sieves, porous zeolites, etc. However, since the pore structure of the porous matrix is ​​still open to the surrounding environment and exposed to the external environment, such as moisture and oxygen, it is necessary to find a suitable porous material to further ensure the stability of perovskite quantum dots.

[0003] At present, in the research on the preparation of perovskite composite materials by encapsulation of porous materials, the porous materials are basically added in the process of synthesizing perovskite by anti-solvent method and hot injection method, and a protective layer covering the perovskite is formed. For example, the Chinese patent with publication number CN115991991A previously applied by the applicant discloses a method for preparing a perovskite quantum dot @ covalent organic framework composite material, which realizes the in-situ growth of perovskite quantum dots on a covalent organic framework by a room temperature anti-solvent method, solves the problem that the existing perovskite quantum dots are easy to decompose under the influence of the external environment, are prone to aggregation fluorescence quenching, and have poor stability, and achieves the purpose of improving the stability of the composite material. Although these methods can provide a strict protective layer for perovskite, it is difficult to control the size of the perovskite, and the stability requirements of the porous material are relatively high.

[0004] Compared with the anti-solvent method and the hot injection method, in the process of synthesizing perovskite composite materials by the light-induced method, the Chinese patent with the authorization announcement number CN113089077A discloses a laser-induced perovskite nucleation crystallization, which uses femtosecond laser to drive the thermophoretic migration of different precursor ions in the solution and material transport methods such as Marangoni convection, and controls the solvent evaporation rate by utilizing the characteristics of the local strong field of the femtosecond laser pulse, thereby realizing the size control of the perovskite nucleation crystallization. However, this laser radiation method not only causes the degradation of the perovskite material and seriously affects the photoelectric conversion efficiency and stability of the device, but also usually requires the introduction of some polar solvents, such as N, N dimethylformamide, dimethyl sulfoxide, etc. The presence of these reagents will cause serious environmental and health problems.

[0005] In this regard, the Chinese patent with the authorization announcement number CN115558137A discloses a method for preparing a flexible perovskite film based on visible light induced self-repairing, which prepares a polymer material containing dynamic diselenide bonds by polymerization reaction, and composites it in the perovskite film, and utilizes the dynamic covalent diselenide bonds at the grain boundaries to break, rearrange and adhere under visible light conditions, so as to obtain a flexible perovskite film. The above method uses mild visible light as the self-repair induction source of the perovskite film, which will not damage the perovskite material and improve the bending resistance and stability of the perovskite film. However, there is still the problem of difficulty in regulating the size of the perovskite, and it is also necessary to introduce reagents that are harmful to the environment and health, such as polytetrahydrofuran, diisocyanate, and organic tin catalyst, which needs to be improved. Summary of the invention

[0006] The problem to be solved by the present invention is to provide a method for preparing perovskite composite materials based on light induction in view of the above-mentioned deficiencies in the prior art, which has the advantages of simple operation, green and environmental protection, ability to improve the stability of the composite material, and easy regulation of the perovskite size.

[0007] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a perovskite composite material based on light induction comprises the following steps:

[0009] preparing a mixed precursor solution comprising lead oleate and cesium oleate;

[0010] After dispersing the covalent organic framework material in a non-polar solvent, adding the mixed precursor solution to continue dispersing, and after the dispersion is completed, post-processing is performed to obtain a mixed precursor powder containing the covalent organic framework material, lead oleate and cesium oleate;

[0011] Adding halogenated alkane to the mixed precursor solution or mixed precursor powder, and reacting under the action of invisible light, and after the reaction, post-processing is performed to obtain the perovskite composite material CsPbX3 NCs or CsPbX3@S-COFs.

[0012] Furthermore, in the step of preparing the mixed precursor solution containing lead oleate and cesium oleate, the mixed precursor solution containing lead oleate and cesium oleate is prepared by reacting cesium acetate and lead acetate in the presence of oleic acid, oleylamine and octadecene after preheating, and post-treating the mixture after the reaction is completed.

[0013] Furthermore, in the step of preparing a mixed precursor solution comprising lead oleate and cesium oleate, the mass ratio of cesium acetate to lead acetate is controlled to be 2-3:4, and the mass volume ratio of lead acetate, oleic acid, oleylamine and octadecene is controlled to be 0.60-1.00 g: 1.50-2.50 mL: 1.50-2.50 mL: 4.50-7.50 mL.

[0014] Furthermore, in the step of preparing a mixed precursor solution containing lead oleate and cesium oleate, the preheating temperature is controlled to be 25-35°C, and during the reaction process, the reaction temperature of the reaction system is first adjusted to 100-120°C in a vacuum atmosphere and maintained for 25-35 minutes to remove moisture and oxygen in the reaction system, and then the reaction temperature of the reaction system is adjusted to 120-140°C in a nitrogen atmosphere and maintained for 25-35 minutes, and then the vacuum-nitrogen cycle is repeated 2-4 times, each time for 4-6 minutes.

[0015] Furthermore, in the step of preparing a mixed precursor powder comprising a covalent organic framework material, lead oleate and cesium oleate, the non-polar solvent is cyclohexane, and the mass volume ratio of the covalent organic framework material, the non-polar solvent and the mixed precursor solution is controlled to be 2~10mg:1~10mL:80~200μL.

[0016] Furthermore, in the step of preparing the mixed precursor powder comprising the covalent organic framework material, lead oleate and cesium oleate, the step includes pre-dispersing 10-30 mg of aldehyde precursor and 10-30 mg of amine precursor in 0.1-10.0 mL of organic solvent by ultrasonic mixing, adding 0.1-3 mL of acid catalyst after ultrasonic dispersion, cooling the reaction solution in liquid nitrogen, degassing by freeze-thaw for 2-4 times, sealing the tube and reacting in an oven at 80-150° C. for 3-7 days, and obtaining the covalent organic framework material by post-treatment after the reaction is completed.

[0017] Furthermore, in the step of preparing the mixed precursor powder comprising the covalent organic framework material, lead oleate and cesium oleate, the mixed precursor solution is added and stirred for 4 to 12 hours to continue dispersion.

[0018] Furthermore, in the step of preparing the perovskite composite material, the halogenated alkane is C 1~10 A combination of one or more of chloroalkanes, bromoalkanes and iodoalkanes.

[0019] Furthermore, in the step of preparing the perovskite composite material, the halogenated alkane is one or a combination of carbon tetrachloride, dibromomethane and 2-iodopropane. By combining and selecting halogenated alkane, CsPbBr3 NCs, CsPbBr x Cl 3-x NCs or CsPbIx Br 3-x NCs.

[0020] Furthermore, in the step of preparing the perovskite composite material, the mass volume ratio of the mixed precursor solution and the halogenated alkane is controlled to be 5~30μL:2~15mL, or the mass volume ratio of the mixed precursor solution and the halogenated alkane used in the mixed precursor powder is controlled to be 80~200μL:2~10mL.

[0021] Furthermore, in the step of preparing the perovskite composite material, the invisible light is ultraviolet light, and the irradiation intensity of the invisible light is controlled to be 60-80%, the irradiation distance is not more than 8 cm, and the irradiation time is 5-25 min.

[0022] Further,

[0023] In summary, the beneficial technical effects of the present invention are:

[0024] 1. The present invention first introduces lead precursors and cesium precursors into the interior of the packaging structure, uses halogenated alkanes as inactive halide sources, and then induces the breaking of the covalent CX bonds of the halogenated alkanes by irradiation with invisible light. The Cs and Pb elements recombine with the halogens separated from the carbon chain in the halogenated alkanes to form bonds, thereby generating CsPbX3 nanocrystals (CsPbX3 NCs). This can prevent high-boiling-point and highly toxic reagents from entering the interior of the packaging material during the lead solidification process and making them difficult to remove. The degree of halogen ion exchange can be precisely controlled by adjusting the photon dose or wavelength of the excitation light. The present invention has the advantages of mild and simple preparation conditions, green and environmental protection, ability to improve the stability of the composite material, and ease of regulating the size of the perovskite.

[0025] 2. The photoinduced method is used to simply and quickly synthesize perovskite, avoiding the introduction of polar solvents with high boiling points and high toxicity during the synthesis process. Specifically, the perovskite is synthesized by adding Cs and Pb sources to a halogenated alkane solution and irradiating it with a UV lamp. In the process of synthesizing pure perovskite, the optical properties of the perovskite are optimized by changing a variety of parameters, such as the amount and ratio of Cs and PbO precursors, and the energy intensity and radiation intensity of the UV lamp;

[0026] 3. In the study of perovskite composite materials, the photoinduced method was used to achieve the in-situ growth of perovskite in the COF pores. The stability test of the obtained perovskite composite material showed that the perovskite composite material had excellent water stability and could be immersed in water for up to half a year. At the same time, COF also played a good protective role for perovskite.

[0027] 4. By combining the prepared perovskite composite material with green fluorescence emission with the preparation of WLED devices, it is shown that the perovskite composite material has potential in lighting display. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the XRD diagram of the composite material CsPbX3 NCs prepared in Example 1 of the present invention.

[0029] Figure 2 TEM images of CsPbX3 NCs prepared in Example 2, Example 11, and Comparative Examples 1 to 3 of the present invention.

[0030] Figure 3 TEM images of CsPbX3 NCs prepared in Example 2, Example 11, and Comparative Examples 4 to 6 of the present invention.

[0031] Figure 4 This is a TEM image of the composite material CsPbX3@S-COF prepared in Example 15 of the present invention.

[0032] Figure 5 It is a TEM image and particle size distribution diagram of the composite material CsPbX3@S-COF prepared in Example 15 of the present invention after one week of water stability test. DETAILED DESCRIPTION

[0033] In order to make the technical means, creative features, objectives and functions achieved by the present invention clearer and easier to understand, the present invention is further explained below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example

[0035] Embodiment 1: A method for preparing a perovskite composite material based on light induction disclosed in the present invention comprises the following steps:

[0036] preparing a mixed precursor solution comprising lead oleate and cesium oleate;

[0037] After dispersing the covalent organic framework material in a non-polar solvent, adding the mixed precursor solution to continue dispersing, and after the dispersion is completed, post-processing is performed to obtain a mixed precursor powder containing the covalent organic framework material, lead oleate and cesium oleate;

[0038] Adding halogenated alkane to the mixed precursor solution or mixed precursor powder, and reacting under the action of invisible light, and after the reaction, post-processing is performed to obtain the perovskite composite material CsPbX3 NCs or CsPbX3@S-COFs.

[0039] Among them, the non-polar solvent is cyclohexane and the halogenated alkane is C 1~10 A combination of one or more of chloroalkanes, bromoalkanes and iodoalkanes.

[0040] Embodiment 2: A method for preparing a perovskite composite material based on light induction disclosed in the present invention is different from Embodiment 1 in that it comprises the following steps:

[0041] S1: First preheat the oil bath to 30°C, weigh 0.38g of cesium acetate and 0.76g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 2.00mL of oleic acid, 2.00mL of oleylamine and 6.00mL of octadecene, and then adjust the reaction temperature of the reaction system to 110°C in a vacuum atmosphere and keep it for 30min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 130°C in a nitrogen atmosphere and keep it for 30min, and finally vacuum-nitrogen cycle 3 times, each time keeping for 5min, to obtain a mixed precursor solution containing lead oleate and cesium oleate in a light yellow oily state; in addition, since lead oleate and cesium oleate are easy to deteriorate at room temperature, after the reaction is completed, the reaction system needs to be cooled, and the mixed precursor solution needs to be sealed and stored in a refrigerator;

[0042] S2 first adds a magnetic stirrer and 5 mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 10 μL of mixed precursor solution. Then, the glass bottle is placed on a stirring table and reacts under ultraviolet light. The ultraviolet light intensity is controlled to be 60%, the irradiation distance is 4 cm, and the irradiation time is 5 min. Then, cyclohexane is added to the reaction solution, and centrifuged at 10000 r / min for 5 min. The supernatant is removed and the precipitate is retained. After the precipitate is dried, the perovskite composite material CsPbBr3NCs is obtained.

[0043] Example 3: A method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is dibromomethane and carbon tetrachloride in a molar ratio of 2:1, and a perovskite composite material CsPbBr2Cl NCs is obtained.

[0044] Example 4: This is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is dibromomethane and carbon tetrachloride in a molar ratio of 1:2 to obtain a perovskite composite material CsPbBrCl2 NCs.

[0045] Example 5: This is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is carbon tetrachloride, and the perovskite composite material CsPbCl3 NCs is obtained.

[0046] Example 6: This is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is dibromomethane and 2-iodopropane in a molar ratio of 2:1 to obtain a perovskite composite material CsPbBr2I NCs.

[0047] Example 7: This is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is dibromomethane and 2-iodopropane in a molar ratio of 1:2 to obtain a perovskite composite material CsPbBrI2 NCs.

[0048] Example 8: This is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the halogenated alkane is 2-iodopropane, and the perovskite composite material CsPbI3 NCs is obtained.

[0049] Example 9: This is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 2 is that 20 μL of mixed precursor solution is added to S2.

[0050] Example 10: This is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that 30 μL of the mixed precursor solution is added to S2.

[0051] Example 11 is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation intensity is 80%.

[0052] Example 12: This is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation distance is 8 cm.

[0053] Embodiment 13 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention, which is different from Embodiment 2 in that it comprises the following steps:

[0054] S1: First preheat the oil bath to 25°C, weigh 0.30g of cesium acetate and 0.60g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 1.50mL of oleic acid, 1.50mL of oleylamine and 4.50mL of octadecene, and then adjust the reaction temperature of the reaction system to 100°C in a vacuum atmosphere and keep it for 25min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 120°C in a nitrogen atmosphere and keep it for 25min, and finally vacuum-nitrogen cycle twice, each time for 4min, to obtain a mixed precursor solution containing lead oleate and cesium oleate in a light yellow oily state; in addition, since lead oleate and cesium oleate are easily deteriorated at room temperature, the mixed precursor solution needs to be sealed and stored in a refrigerator after the reaction is completed and the reaction system is cooled;

[0055] S2 first adds a magnetic stirrer and 2 mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 5 μL of mixed precursor solution. Then, the glass bottle is placed on a stirring table and reacts under ultraviolet light. The ultraviolet light intensity is controlled to be 60%, the irradiation distance is 2 cm, and the irradiation time is 10 min. Then, cyclohexane is added to the reaction solution, and centrifuged at 10000 r / min for 5 min. The supernatant is removed and the precipitate is retained. After the precipitate is dried, the perovskite composite material CsPbBr3NCs is obtained.

[0056] Example 14: A method for preparing a perovskite composite material based on light induction disclosed in the present invention, which is different from Example 2 in that it includes the following steps:

[0057] S1: First preheat the oil bath to 35°C, weigh 0.50g of cesium acetate and 1.00g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 2.50mL of oleic acid, 2.50mL of oleylamine and 7.50mL of octadecene, and then adjust the reaction temperature of the reaction system to 120°C in a vacuum atmosphere and keep it for 35min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 140°C in a nitrogen atmosphere and keep it for 35min, and finally vacuum-nitrogen cycle 4 times, each time for 6min, to obtain a mixed precursor solution containing lead oleate and cesium oleate in a light yellow oily state; in addition, since lead oleate and cesium oleate are easily deteriorated at room temperature, the mixed precursor solution needs to be sealed and stored in a refrigerator after the reaction is completed and the reaction system is cooled;

[0058] S2 first adds a magnetic stirrer and 15 mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 30 μL of mixed precursor solution. Then, the glass bottle is placed on a stirring table and reacts under ultraviolet light. The ultraviolet light intensity is controlled to be 80%, the irradiation distance is 8 cm, and the irradiation time is 15 min. Then, cyclohexane is added to the reaction solution, and centrifuged at 10,000 r / min for 5 min. The supernatant is removed and the precipitate is retained. After drying the precipitate, the perovskite composite material CsPbBr3NCs is obtained.

[0059] Embodiment 15 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention, which is different from Embodiment 1 in that it comprises the following steps:

[0060] S1: First preheat the oil bath to 30°C, weigh 0.57g of cesium acetate and 0.76g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 2.00mL of oleic acid, 2.00mL of oleylamine and 6.00mL of octadecene, and then adjust the reaction temperature of the reaction system to 110°C in a vacuum atmosphere and keep it for 30min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 130°C in a nitrogen atmosphere and keep it for 30min, and finally vacuum-nitrogen cycle 3 times, each time keeping it for 5min, to obtain a mixed precursor solution containing lead oleate and cesium oleate in a light yellow oily state; in addition, since lead oleate and cesium oleate are easy to deteriorate at room temperature, after the reaction is completed, the reaction system needs to be cooled, and the mixed precursor solution needs to be sealed and stored in a refrigerator;

[0061] S2 According to the method of Example 1 of CN115991991A, 0.05mmol of aldehyde precursor and 0.05mmol of amine precursor were put into a glass bottle, and then 1mL of mesitylene and 0.5mL of dioxane were added. After the solution was ultrasonicated to a turbid solution, it was transferred to a vacuum tube, and 6M and 0.15mL of acetic acid catalyst were added. The vacuum tube was quickly frozen and evacuated with 77K liquid nitrogen, and freeze-thawed and degassed 3 times, then sealed, and placed at 120°C for 3 days. After the reaction was completed, the solid was separated by centrifugation and washed with acetone. Then the sample was transferred to a vacuum oven and evacuated at 50°C for 6h to obtain a covalent organic framework material;

[0062] S3 first adds 5 mg of the covalent organic framework material prepared in S2 into a small glass bottle containing 3 mL of cyclohexane, and then adds 140 μL of the mixed precursor solution prepared in S1, and then places it on a stirring table and stirs for 12 hours. After the covalent organic framework material is stirred until the solid particles are completely dispersed, the solution is evaporated to dryness to obtain a mixed precursor powder;

[0063] S4 first adds a magnetic stirrer and 5 mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 140 μL of mixed precursor solution, and then places the glass bottle on a stirring table and reacts under ultraviolet light, controlling the ultraviolet light intensity to 60%, the irradiation distance to 4 cm, and the irradiation time to 20 min. Then, cyclohexane is added to the reaction solution, and centrifuged at 10000 r / min for 5 min, the supernatant is removed, and the precipitate is retained. After drying the precipitate, the perovskite composite material CsPbX3@S-COFs is obtained.

[0064] Example 16: This is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 15 is that 60 μL of mixed precursor solution is added to S4.

[0065] Example 17: This is a method for preparing perovskite composite materials based on light induction disclosed in the present invention. The difference from Example 15 is that in S4, 100 μL of mixed precursor solution is added.

[0066] Embodiment 18 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention, which is different from Embodiment 15 in that it comprises the following steps:

[0067] S1: Preheat the oil bath to 25°C, weigh 0.45g of cesium acetate and 0.60g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 1.50mL of oleic acid, 1.50mL of oleylamine and 4.50mL of octadecene, and then adjust the reaction temperature of the reaction system to 100°C in a vacuum atmosphere and keep it for 25min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 120°C in a nitrogen atmosphere and keep it for 25min, and finally vacuum-nitrogen cycle twice, each time for 4min, to obtain a light yellow oily mixed precursor solution containing lead oleate and cesium oleate; in addition, since lead oleate and cesium oleate are easy to deteriorate at room temperature, after the reaction is completed, the reaction system needs to be cooled, and the mixed precursor solution needs to be sealed and stored in a refrigerator;

[0068] S2 According to the method of Example 1 of CN115991991A, 0.05mmol of aldehyde precursor and 0.05mmol of amine precursor were put into a glass bottle, and then 1mL of mesitylene and 0.5mL of dioxane were added. After the solution was ultrasonicated to a turbid solution, it was transferred to a vacuum tube, and 6M and 0.15mL of acetic acid catalyst were added. The vacuum tube was quickly frozen and evacuated with 77K liquid nitrogen, and freeze-thawed and degassed 3 times, then sealed, and placed at 120°C for 3 days. After the reaction was completed, the solid was separated by centrifugation and washed with acetone. Then the sample was transferred to a vacuum oven and evacuated at 50°C for 6h to obtain a covalent organic framework material;

[0069] S3 first adds 2 mg of the covalent organic framework material prepared in S2 into a small glass bottle containing 1 mL of cyclohexane, and then adds 80 μL of the mixed precursor solution prepared in S1, and then places it on a stirring table and stirs for 4 hours. After the covalent organic framework material is stirred until the solid particles are completely dispersed, the solution is evaporated to dryness to obtain a mixed precursor powder;

[0070] S4 first adds a magnetic stirring bar and 2 mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 80~200 μL of mixed precursor solution. Then, the glass bottle is placed on a stirring table and reacts under ultraviolet light. The ultraviolet light intensity is controlled to be 60%, the irradiation distance is 2 cm, and the irradiation time is 18 min, until the reaction liquid turns yellow-green. Then, cyclohexane is added to the reaction liquid, and centrifuged at 10000 r / min for 5 min. The supernatant is removed and the precipitate is retained. After the precipitate is dried, the perovskite composite material CsPbX3@S-COFs is obtained.

[0071] Embodiment 19 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention, which is different from Embodiment 15 in that it comprises the following steps:

[0072] S1: First preheat the oil bath to 35°C, weigh 0.75g of cesium acetate and 1.00g of lead acetate and add them to a 50mL single-necked flask, then fix the flask in the oil bath, add 2.50mL of oleic acid, 2.50mL of oleylamine and 7.50mL of octadecene, and then adjust the reaction temperature of the reaction system to 120°C in a vacuum atmosphere and keep it for 35min to remove moisture and oxygen in the reaction system, then adjust the reaction temperature of the reaction system to 140°C in a nitrogen atmosphere and keep it for 35min, and finally vacuum-nitrogen cycle 4 times, each time for 6min, to obtain a mixed precursor solution containing lead oleate and cesium oleate in a light yellow oily state; in addition, since lead oleate and cesium oleate are easily deteriorated at room temperature, the mixed precursor solution needs to be sealed and stored in a refrigerator after the reaction is completed and the reaction system is cooled;

[0073] S2 According to the method of Example 1 of CN115991991A, 0.05mmol of aldehyde precursor and 0.05mmol of amine precursor were put into a glass bottle, and then 1mL of mesitylene and 0.5mL of dioxane were added. After the solution was ultrasonicated to a turbid solution, it was transferred to a vacuum tube, and 6M and 0.15mL of acetic acid catalyst were added. The vacuum tube was quickly frozen and evacuated with 77K liquid nitrogen, and freeze-thawed and degassed 3 times, then sealed, and placed at 120°C for 3 days. After the reaction was completed, the solid was separated by centrifugation and washed with acetone. Then the sample was transferred to a vacuum oven and evacuated at 50°C for 6h to obtain a covalent organic framework material;

[0074] S3 first adds 10 mg of the covalent organic framework material prepared in S2 into a small glass bottle containing 10 mL of cyclohexane, and then adds 200 μL of the mixed precursor solution prepared in S1, and then places it on a stirring table and stirs for 12 hours. After the covalent organic framework material is stirred until the solid particles are completely dispersed, the solution is evaporated to dryness to obtain a mixed precursor powder;

[0075] S4 first adds a magnetic stirrer and 2~10mL of halogenated alkane into a glass bottle, the halogenated alkane is dibromomethane, and then adds 80~200μL of mixed precursor solution, and then places the glass bottle on a stirring table and reacts under ultraviolet light, controlling the ultraviolet light intensity to 80%, the irradiation distance to 8cm, and the irradiation time to 25min until the reaction liquid turns yellow-green, then adds cyclohexane to the reaction liquid, and centrifuges at 10000r / min for 5min, removes the supernatant, retains the precipitate, and after drying the precipitate, obtains the perovskite composite material CsPbX3@S-COFs.

[0076] Comparative Example

[0077] Comparative Example 1 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation intensity is 20%.

[0078] Comparative Example 2 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation intensity is 40%.

[0079] Comparative Example 3 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation intensity is 100%.

[0080] Comparative Example 4 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation distance is 12 cm.

[0081] Comparative Example 5 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation distance is 16 cm.

[0082] Comparative Example 6 is a method for preparing a perovskite composite material based on light induction disclosed in the present invention. The difference from Example 2 is that in S2, the irradiation distance is 20 cm.

[0083] Performance testing

[0084] (1) In order to characterize the crystal parameters of CsPbBr3 NCs, the CsPbBr3 NCs prepared in Example 2 were subjected to XRD detection. The detection results are as follows: Figure 1 shown.

[0085] from Figure 1 It can be seen that the (100), (110), (220), (201), (211) and (202) crystal planes of CsPbBr3 NCs correspond to the corresponding diffraction peaks, and they also correspond to the diffraction peaks of the standard CsPbBr3 PDF card, proving that CsPbBr3 is generated. The emission peak of CsPbBr3 NCs is at 500nm, and the corresponding half-peak width is 25nm. In addition, there is a very small emission peak in the wavelength range of 430~450nm, which may be another form of CsPbBr3 NCs; the position of the UV absorption peak is around 487nm.

[0086] (2) According to the methods of Example 2, Example 11, and Comparative Examples 1 to 3, a UV lamp with a maximum energy intensity (100% energy intensity) of 1400 mW was used for light induction, and the properties of the synthesized CsPbBr3 NCs solution were detected when the UV lamp irradiation intensity was 20%, 40%, 60%, 80% and 100%, respectively. When the UV lamp irradiation energy intensity was different, the generated CsPbBr3 NCs all had strong green fluorescence emission. The TEM images of the prepared CsPbBr3 NCs are shown in FIG. Figure 2 shown.

[0087] from Figure 2It can be seen that the synthesized CsPbBr3 NCs are in a state where nanowires and QDs coexist. In addition to being generated during light induction, nanowires may also be generated through self-assembly after synthesis, so the number gradually increases. When the energy intensity of the UV lamp is 20% and 40%, only nanowires are seen in the TEM image, and there are almost no QDs. It may be that QDs grow into nanowire morphology through self-assembly in the later stage; when the energy intensity of the UV lamp is 60% and 80%, in addition to nanowires, the number of QDs in the TEM image gradually increases, corresponding to the existence of two emission peaks in PL, indicating that as the energy intensity of UV lamp irradiation increases, the number of QDs also increases.

[0088] (3) According to the method of Example 2, Example 12, and Comparative Examples 4 to 6, the radiation intensity of the UV lamp was changed by adjusting the irradiation distance to perform light induction, and the performance of the synthesized CsPbBr3 NCs solution was detected when the UV lamp irradiation distance was 4, 8, 12, 16, and 20 cm. When the UV lamp irradiation distance was different, the generated CsPbBr3 NCs all had strong green fluorescence emission, and as the irradiation distance increased, the color of the CsPbBr3 NCs solution became clearer and clearer. This is because as the irradiation distance increased, the UV lamp radiation intensity decreased, resulting in fewer and fewer NCs being generated. The TEM image of the prepared CsPbBr3 NCs is shown in FIG. Figure 3 shown.

[0089] from Figure 3 It can be seen that as the UV light irradiation distance increases from 4cm to 20cm, the ratio of nanowires and QDs in CsPbBr3 NCs changes significantly. At 4cm, the number of nanowires and QDs is large; at 8cm, it can be clearly observed that the number of nanowires decreases; at 12cm and 16cm, no QDs are observed in the TEM image, and only a small amount of nanowires exists; at 20cm, neither nanowires nor QDs are generated, and only nanosheets exist, and the size of these nanosheets is about 70nm.

[0090] (4) The microstructure of the perovskite composite material CsPbBr3@S-COF prepared in Example 15 was tested. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that some small-sized QDs are mixed with rectangular and round large NCs. It can be considered that these small QDs are in the pores, while these large NCs are embedded in the interlayers of S-COFs.

[0091] (5) The microstructure of the perovskite composite material CsPbBr3@S-COF prepared in Example 15 was tested after one week of water stability test. The results are as follows: Figure 5 As shown. Figure 5It can be seen that after the water stability test, the size of CsPbBr3 NCs in the composite material tends to increase, and the average size increases from 2.92nm at the beginning to 3.17nm, which is almost equal to the pore diameter of S-COFs. This shows that the pore structure of COFs has a protective effect on CsPbBr3 QDs.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a perovskite composite material based on light induction, characterized in that: The following steps are included: preparing a mixed precursor solution comprising lead oleate and cesium oleate; After dispersing the covalent organic framework material in a non-polar solvent, adding the mixed precursor solution to continue dispersing, and after the dispersion is completed, post-processing is performed to obtain a mixed precursor powder containing the covalent organic framework material, lead oleate and cesium oleate; Adding halogenated alkane to the mixed precursor powder, reacting under the action of invisible light, and post-processing after the reaction to obtain the perovskite composite material CsPbX3@S-COFs; In the step of preparing the mixed precursor solution containing lead oleate and cesium oleate, the steps include: reacting cesium acetate and lead acetate in the presence of oleic acid, oleylamine and octadecene after preheating, and performing post-treatment after the reaction to obtain a mixed precursor solution containing lead oleate and cesium oleate; In the step of preparing a mixed precursor solution containing lead oleate and cesium oleate, the mass ratio of cesium acetate to lead acetate is controlled to be 2-3:4, and the mass volume ratio of lead acetate, oleic acid, oleylamine and octadecene is controlled to be 0.60-1.00 g: 1.50-2.50 mL: 1.50-2.50 mL: 4.50-7.50 mL; In the step of preparing a mixed precursor powder comprising a covalent organic framework material, lead oleate and cesium oleate, 0.05 mmol of an aldehyde precursor and 0.05 mmol of an amine precursor are put into a glass bottle, and then 1 mL of mesitylene and 0.5 mL of dioxane are added, the solution is ultrasonicated to a turbid solution, and then transferred to a vacuum tube, and 6 M and 0.15 mL of acetic acid catalyst are added, and the vacuum tube is rapidly frozen and degassed using 77K liquid nitrogen, and freeze-thawed and degassed 3 times, and then sealed, and placed at 120° C. for 3 days. After the reaction is completed, the solid is separated by centrifugation and washed with acetone, and then the sample is transferred to a vacuum oven and vacuumed at 50° C. for 6 hours to obtain a covalent organic framework material; In the step of preparing a mixed precursor powder comprising a covalent organic framework material, lead oleate and cesium oleate, the non-polar solvent is cyclohexane, and the mass volume ratio of the covalent organic framework material, the non-polar solvent and the mixed precursor solution is controlled to be 2-10 mg: 1-10 mL: 80-200 μL; In the step of preparing the perovskite composite material, the halogenated alkane is C 1~10 One or more combinations of chloroalkanes, bromoalkanes and iodoalkanes; In the step of preparing the perovskite composite material, the mass volume ratio of the mixed precursor solution and the halogenated alkane used in the mixed precursor powder is controlled to be 80-200 μL: 2-10 mL; In the step of preparing the perovskite composite material, the invisible light is ultraviolet light.

2. The method for preparing a perovskite composite material based on light induction according to claim 1, characterized in that: In the step of preparing a mixed precursor solution containing lead oleate and cesium oleate, the preheating temperature is controlled to be 25-35° C., and during the reaction process, the reaction temperature of the reaction system is first adjusted to 100-120° C. in a vacuum atmosphere and maintained for 25-35 minutes to remove moisture and oxygen in the reaction system, and then the reaction temperature of the reaction system is adjusted to 120-140° C. in a nitrogen atmosphere and maintained for 25-35 minutes, and then the vacuum-nitrogen cycle is repeated 2-4 times, each time maintained for 4-6 minutes.

3. The method for preparing a perovskite composite material based on light induction according to claim 1, characterized in that: In the step of preparing the mixed precursor powder comprising the covalent organic framework material, lead oleate and cesium oleate, the mixed precursor solution is added and stirred for 4 to 12 hours to continue dispersion.

4. The method for preparing a perovskite composite material based on light induction according to claim 1, characterized in that: In the step of preparing the perovskite composite material, the irradiation intensity of the invisible light is controlled to be 60-80%, the irradiation distance is not more than 8 cm, and the irradiation time is 5-25 min.

Citation Information

Patent Citations

  • Laser-induced nucleation crystallization of perovskite

    CN113089077A

  • Preparation method of flexible perovskite thin film based on visible light induced self-repairing

    CN115558137A

  • Preparation method of perovskite quantum dot and covalent organic framework composite material

    CN115991991A

  • Preparation method of dimension-controllable CsPbX3 perovskite nanometer crystals

    CN108101102A

  • Preparation and application of full-inorganic perovskite quantum dot / mesoporous MOF-5 composite luminescent material in LED (Light-emitting Diode)

    CN108774511A